Maternal dietary glycemic index and glycemic load and later risk of obesity: a review of the evidence - Shojaei Zarghani, Sara; Alizadeh, Mohammad (Progress in Nutrition, 2019)
In view of the rising globalization of obesity, numerous studies have been performed to determine the risk factors of this epidemic. Mounting evidence suggests maternal nutrition during pregnancy may have profound effects on adult’s obesity. This study aimed to summarize the current evidence regarding the association between maternal dietary glycemic index (GI) and glycemic load (GL) and obesity risk in later life, either in childhood or adulthood. A literature search using scientific databases was conducted without restriction. Included studies (n=9) were a combination of observational, interventional and animal investigations. Among human studies, one observational and two interventional studies showed a positive and others found no or negative (n=1) association between maternal dietary GI and offspring anthropometric parameters at different ages; although sometimes it was dependent to sex or timing of the maternal exposure to high GI and GL. Two of the included studies, which were animal based, also showed a beneficial effect of maternal low GI on postnatal growth rates and adiposity. Maternal low GI and GL probably have favorable effects on later obesity risk; however, the present research findings are not sufficient to conclude an approved association. More studies are necessary for scrutiny judging about the effectiveness of maternal GI and GL on offspring obesity.